Simulation Analysis of Prototype Filter Bank Multicarrier Cognitive Radio Under Different Performance Parameters - A.S Kang; Renu Vig (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
Cognitive Radio has proven as a optimum technique for getting improved spectrum utilization by sharing the radio spectrum with licensed primary users opportunistically. The cognitive radio is a new paradigm to overcome the persisting problem of spectrum underutilization.Seeing the everincreasing demand of wireless applications,the radio sp ectrum is a valuable resource and in cognitive radio systems,trustworthy spectrum sensing techniques are required to avoid any harmful interference to the primary users.As cognitive radio possess the capability to utilise the unused spectrum holes or white spaces so,there is a tremendous need to scan the large range of spectrum either for interference management or for primary receiver detection.Dynamic Spectrum Access techniques need to be implemented for the sake of better radio resource management and computational complexity analysis of multirate filter bank cognitive radio,where BER and Eb/No are the performance metrics or governing parameters to affect the system performance using polyphase filter bank.The present paper deals with the study of effect of variation of number of subchannels M at fix overlapping factor K of polyphase component of Filter Bank Multicarrier cognitive radio in terms of prototype filter length at Lp=K*M .